Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.17988/bedi-41-04-241-257.1
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Risk through a Supplementary Reading Intervention: A Case Study of First- and Second-Grade Urban Students

Abstract: This descriptive study examined whether a computer-based, repeated reading intervention (i.e., Reading Relevant and Culturally Engaging Stories) is associated with improved reading and social behavior for three primary-aged urban black girls who each showed both academic and behavioral risk. The Reading Relevant and Culturally Engaging Stories intervention utilized culturally relevant reading passages for repeated readings delivered through computer software to increase the reading fluency of the young learner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Barber (2015) and Green (2015) utilized an updated version of the RR program, which afforded more student independence, to increase the ORF of first-grade African American and Somali background students. Other subsequent studies with this population showed similar student gains for second graders partially supervised by a paraprofessional (Council, 2016) and for primary-aged students with attention deficits and behavior disorders (Council, Cartledge, Green, Barber, & Gardner, 2016).…”
Section: Previous Research On Reading Races (Rr)mentioning
confidence: 65%
“…Barber (2015) and Green (2015) utilized an updated version of the RR program, which afforded more student independence, to increase the ORF of first-grade African American and Somali background students. Other subsequent studies with this population showed similar student gains for second graders partially supervised by a paraprofessional (Council, 2016) and for primary-aged students with attention deficits and behavior disorders (Council, Cartledge, Green, Barber, & Gardner, 2016).…”
Section: Previous Research On Reading Races (Rr)mentioning
confidence: 65%
“…Through a series of studies, Cartledge and colleagues provide an example specific to reading instruction (Cartledge et al, 2015; Cartledge, Keesey, et al, 2016; Council et al, 2016; Talesman et al, 2019). Recognizing the research evidence on the effectiveness of repeated reading to improve reading fluency and reading comprehension and on the use of culturally relevant practices to support learning and achievement among diverse learners, the research team worked to embed both within a Response to Intervention/Multi‐Tiered Systems of Support framework for first‐ and second‐grade students in urban schools.…”
Section: Accept That Complex Problems Deserve Comprehensive Solutionsmentioning
confidence: 99%
“…It is suggested that the fifth-grade students should master the skills to read with unfamiliar words and determine the meaning of words through context [47]. Furthermore, it is essential for intermediate-grade students to acquire the ability to analyze, make inferences, and draw conclusions on a wide range of literacy forms, such as poetry, fiction, drama, or media, for passing the test, which is a big challenge for ELs [48,49]. According to the Texas State Literacy Plan (TSLP), it is important to prepare every single student in Texas to be well-prepared for the literacy demand of college and/or their future careers after they graduate from high school.…”
Section: Texas-mexico Border School Students' Reading Achievementmentioning
confidence: 99%